Validation of Kala-azar diagnostic tests in a pediatric teaching hospital in Baghdad. - Al-Janabi, Muhi K.; Nasir, Nadia A.; Hameed, Ammar A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Kala-azar is an important parasitic disease that affects children of all age groups with fatal outcome if left without treatment.Objectives: Children admitted with Kala-azar were studied for evaluation of Indirect Immunoflorescent Antibody Test and Bone Marrow examination validity.Results: The majority (94%) of studied children were less than 5 years age group. Males were more than females with a ratio of 1.63:1. Sixty percent of patients were from Diyala governorate and 23% from Baghdad. The main clinical features were prolonged fever and hepatosplenomegaly (100%). Bone marrow examination was positive in 45% of suspected Kala-azar cases. IFAT was positive in 47(78%). IFAT sensitivity was 70% and specificity 15%. All cases were treated with Pentostam (sodium stibogluconate). No resistance to Pentostam treatment was detected. The case mortality rate was 2%.Patients and methods: A cross-sectional study was conducted on 60 children with Kala-azar admitted to Children Welfare Teaching Hospital - Medical City - Baghdad, for the period from the 1st of January 2011 to the 1st of February 2012. Information was obtained for each child including age, sex, residence, signs and symptoms, laboratory investigations and diagnosis was established by serology and/or bone marrow examination. Treatment and outcome were also noted.Conclusion: The highest sensitivity in laboratory diagnosis among studied children was that obtained with a combination of bone marrow aspirate direct examination and IFAT. Conventional methods for diagnosis of visceralLeishmaniasis are still indispensable.